Analysis of the Level of Vulnerability to Floods using the Method of Simple Moving Average (A Case Study of the City of Padang) - Shary Lusinia; Nugraha Rahmansyah (Universitas Putra Indonesia YPTK Padang, 2020)
Flood is the overflow of the river flow due to water exceed the storage capacity of the river, so that overflow and inundate the plains or the lower regions in the vicinity. Floods are natural disasters that often occur in Indonesia because it is located in the tropics. A lot of flood prone areas which have high population density, due to less understanding of the community regarding the geographic region. Floods often occur in the City of Padang caused by high rainfall in the upstream areas of the river and the topography is hilly so increase the speed of the flow of water to the lower plains. In this study, the author examines the factors of vulnerability to flood by using the method of Simple Moving Average with a parameter of the flood that used rainfall and long rainy days.